2020
DOI: 10.3934/jdg.2020018
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of semialgebraic gene-environment networks

Abstract: Gene-environment network studies rely on data originating from different disciplines such as chemistry, biology, psychology or social sciences. Sophisticated regulatory models are required for a deeper investigation of the unknown and hidden functional relationships between genetic and environmental factors. At the same time, various kinds of uncertainty can arise and interfere with the system's evolution. The aim of this study is to go beyond traditional stochastic approaches and to propose a novel framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Application of uncertainty and forecasting techniques such as robust optimization (Golpîra and Tirkolaee, 2019; Kara et al, 2019; Khalilpourazari et al, 2020a; Lotfi et al, 2020; Özmen et al, 2017), fuzzy programming (Goli et al, 2021; Maity et al, 2019; Roy et al, 2019; Tirkolaee et al, 2021), stochastic optimal control (Kalaycı et al, 2020; Kropat et al, 2020; Savku and Weber, 2018), time series (Weber et al, 2011), regression models (Kuter et al, 2018), and grey systems (Ergün et al, 2020) to address the uncertain nature of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Application of uncertainty and forecasting techniques such as robust optimization (Golpîra and Tirkolaee, 2019; Kara et al, 2019; Khalilpourazari et al, 2020a; Lotfi et al, 2020; Özmen et al, 2017), fuzzy programming (Goli et al, 2021; Maity et al, 2019; Roy et al, 2019; Tirkolaee et al, 2021), stochastic optimal control (Kalaycı et al, 2020; Kropat et al, 2020; Savku and Weber, 2018), time series (Weber et al, 2011), regression models (Kuter et al, 2018), and grey systems (Ergün et al, 2020) to address the uncertain nature of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the application of the hostility measure in those fields, it could also perform in different domains like, for example, Big Data, to check if the condensation of data is rich enough to substitute the original data [12]. Also, an adapted version of the hostility could be applied to obtain useful information to enrich the modeling phase in targetenvironment networks that arises in fields like genetics and economics [19].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Tirkolaee et al [53] identified the contributions of ML techniques in selecting and segmenting suppliers, predicting supply chain risks, and estimating demand and sales, production, inventory management, transportation and distribution, sustainable development (SD), and circular economy (CE). Kropat et al [54] proposed a novel framework of semialgebraic gene-environment networks. Khalilpourazari and Doulabi [55] showed that the offered robust model handles uncertainties more efficiently and finds solutions that have significantly lower costs and delivery time.…”
Section: Supply Chainmentioning
confidence: 99%